Perlindungan Hukum Terhadap Pemegang Merek Clothing - I Made Agus Angga Kusuma Putra; Anak Agung Istri Agung; Desak Gde Dwi Arini (Jurnal Interpretasi Hukum, 2021)
Trademarks are one of the most disputed intellectual property rights. The number of brand counterfeiting events conducted to gain profit by shortcuts, namely by violating business ethics, norms, and laws certainly do not make trade good and worsen the image as a violation of IPR. The purposes of this research are to examine the form of legal protection against registered clothing brand holders and to analyze the legal consequences for businesses that market clothing brands without a license? This research uses normative legal research methods by using statutory approach. Law No. 20 of 2016 and Law No. 5 of 1999 source to know criminal sanctions and also civil sanctions against businesses that use the brand without a permit. The results of this study show a form of legal protection against registered brand holders in the form of exclusive rights granted by the state to registered brand owners. Legal consequences for businesses that market brands without a license can be penalized as follows, in article 382bis criminal code can also be penalized i.e. material acts are threatened with a maximum prison sentence of one year and a fine as high as nine hundred million rupiah.